A gilded lady [large type] - Camden, Elizabeth, 1965- (Camden, Elizabeth, 1965- Hope and glory, 2021)
Caroline Delacroix is at the pinnacle of Washington high society in her role as secretary to the first lady of the United States. But she's hiding a terrible secret. If she cannot untangle a web of foreign espionage, her brother will face execution for treason. Nathaniel Trask is the new head immediately suspicious of Caroline despite his overwhelming attraction to her quick wit and undeniable charm. Amid the glamorous pageantry of Gilded Age Washington, DC, Caroline and Nathaniel will face adventure, danger, and heartbreak in a race against time that will span the continent. - back cover.